Screening of Sri Lankan rice (Oryza sativa L.) landraces for drought tolerance - S. P. Munasinghe; S. Somaratne; S. R. Weerakoon (Tropical Agricultural Research, 2017)
Twenty four (24) traditional Sri Lankan rice landraces were screened for drought tolerance at seedling stage in the greenhouse at the Open University of Sri Lanka, Nawala. Four week old seedlings grown in pots filled with soil were exposed to drought condition by disconnecting water supply for two weeks. Drought tolerance was evaluated by measuring plant height and leaf width after two weeks of recovery. Agro-morphological characterization of rice landraces was made on vegetative characters and yield attributed characters. The Simple Sequence Repeat (SSR) marker analysis was employed to determine the association between allelic diversity and drought tolerance of traditional rice landraces. Comparatively, the landraces Suwandal, Kirimurunga and Suduru samba showed tolerance to drought. Meanwhile, the SSR marker RM252 have shown the potential candidacy for tracing drought tolerance compared to other markers used in the study.